Pengaruh Profitabilitas, Ukuran Perusahaan, Capital Intensity Dan Kepemilikan Institusional Terhadap Agresivitas Pajak Pada Perusahaan Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Lukita, Jocelynn; Wijaya, Yohana Alya; Guandinata, Veronica; Aruan, Deasy Arisandy; Putri, Ilfi Rahmi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to test and analyze the influence of Profitability, Company Size, Capital Intensity and Institutional Ownership on Tax Aggressiveness in Consumer Companies Listed on the Indonesia Stock Exchange in 2017-2021. This research method uses quantitative research. The population using all consumer goods companies on the Indonesian Stock Exchange is 78 companies. The samples obtained were 29 companies using purposive sampling technique. The statistical method is multiple linear regression analysis. The t test shows that Capital Intensity has an effect on Tax Aggressiveness. However, profitability, company size and institutional ownership have no effect on tax aggressiveness. And the F test shows that Profitability, Company Size, Capital Intensity and Institutional Ownership have no effect on Tax Aggressiveness. The coefficient of determination is 4.2% and the remaining 95.8% is explained by other variables that are not included in the research model. The conclusion of this research is that only partial Capital Intensity has an effect on Tax Aggressiveness in Consumer Companies listed on the Indonesian Stock Exchange in 2017-2021, while simultaneous test , Profitability, Company Size, Capital Intensity and Institutional Ownership has no effect on Tax Aggressiveness in Consumer Companies listed on the Indonesian Stock Exchange in 2017-2021.